Mammalian genomics (CABI Pub., 2005)
Genomics has experienced a dramatic development during the last 15-20 years. Data from mammalian genomes such as the human, mouse, and rat have already been published, while others such as the dog, cattle and chimpanzee will soon follow. This book summarizes the current knowledge of mammalian